NINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN MENGGUNAKAN COOPERATIVE LEARNING TIPE THINK PAIR SHARE - Mutia, Evita (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research base of fact in field that study of IPS in Class IV SDN 05 Taram Kabupaten 50 Kota, Teacher still predominate studies process and cannot entangle student participation directly. The condition result make lower result of learning study of IPS as according to KKM which have been specified that is 70. Therefore not conducted by research with aim to increase result of learning IPS by using Model Cooperative Learning Type The Power Two of according to Silberman (2007:161) in Class IV SDN 05 Taram Kabupaten 50 Kota. That research use Approach qualitative and is quantitative, while this Type research that is Action Researchs Kata Kunci: hasil belajar; pembelajaran IPS ;cooperative learning type think pair share.